Control of Oligomerization and Oxidation Steps in the Synthesis of Tris(pentafluorophenyl)corrole. Issue 14 (1st April 2015) - Blumenfeld, Carl; Fisher, Katherine J.; Henling, Lawrence M.; Grubbs, Robert H.; Gray, Harry B.; Virgil, Scott C.
Abstract: The mechanistic features of oligomerization and oxidative cyclization steps in the synthesis of tris(pentafluorophenyl)corrole (1 ) have been thoroughly studied. Separation of the intermediates by preparative HPLC and analysis by NMR spectroscopy and high resolution mass spectrometry allowed for the identification of product‐forming intermediates and monitoring of undesired byproducts. Conditions for complete end‐capping with pyrrole were optimized for improved yields of oligomers leading to the desired corrole1 . A yield of 84 % was achieved during oxidation of an isolated precursor; the overall yield of1 was 17.0 %. Abstract : The mechanistic features of oligomerization and oxidative cyclization steps in the synthesis of tris(pentafluorophenyl)corrole (1 ) are presented. Analysis of isolated intermediates allowed for the identification of conditions for complete end‐capping with pyrrole. Conditions were also optimized for the controlled oxidation to the desired corrole1 . An 84 % yield was achieved during oxidation of the isolated precursor6 and a 17 % overall yield of1 was achieved on scale.